IMPROVING STUDENTS' PROBLEM-SOLVING SKILLS THROUGH THE IMPLEMENTATION OF LEARNING REPORT ASSISTED LEARNING (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2023)
One of the electronic learning applications that has been widely used in learning is Google Classroom. This study reports the implementation of an application used to report learning outcomes from Google Classroom, namely Learning Report. The application was used to monitor the progress of student learning activities. To determine the impact of using student learning activity monitoring applications on student learning outcomes, the learning outcomes of two groups of students (control class and experimental class) were compared. Learning improvements were found in both classes, but higher improvements were found in students monitoring their learning with the Learning Reports Application.
Keywords: google classroom; problem based learning; problem solving skills